La atenuación mediante la partícula discursiva ¿eh? en el lenguaje adolescente de Madrid - Jørgensen, Annette Myre (Bergen Language and Linguistics Studies, 2019)
The discourse particle eh has a high frequency in the Madrid teenage talk. The different functions this short particle displays in the interaction, as for instance: calling upon the hearer’s attention, demanding approval or asking for a repetition of what is said, or hedging is worth some attention. One of the many functions attributed to this particle is the hedging one, especially when there are utterances containing speech acts conveying orders, critics and recriminations, which could imply a face threat. This paper will therefore describe the hedging function of the final interrogative ¿eh? in the oral speech among Madrid teenagers. Hedging is a pragmatic strategy by which the speaker minimizes the effects of the utterance. It can have impact on different elements in the communicative process: the message, the speaker, the hearer and the relation between both. Although teenagers are not known for their tendency to soften the content and effect of their sayings, there are several utterances among the Madrid teenagers that present a certain hedging through the particle ¿eh? in a final position. The examples used in this study are extracted from the Corpus Oral de Lenguaje Aolescente, COLA-corpus (http://www.colam.org/), which contains spontaneous, informal teenage (13 to 19 years) talk from Madrid. There are more than 5000 concordances with ¿eh? displaying a wide array of functions in different positions in the utterance. The cases that have ¿eh? in a final position and a hedging function have been selected for the analysis of this paper.